Effects of Opium Dependency on Testicular Tissue in a Rat Model: An Experimental Study - Jamshidian, Hassan; Amini, Erfan; Karvar, Mohsen; Ayati, Elnaz; Ayati, Mohsen; Pishgar, Farhad; Jamali Zavarehei, Mansoor; Azmoudeh Ardalan, Farid; Khazaeipour, Zahra; Amanpour, Saeid; et al. (Urology Journal, 2019)
Purpose: This study is aimed to evaluate the effects of opium dependency on testicular tissue in a rat model. Methods: Thirty-two Wistar male rats (aged 30 days and weighing 200-250 grams) were randomized into two groups. Group A, consisting of 16 rats, received dissolved oral opium tablets in drinking water for 45 days, whereas group B (control group) consisted of 16 rats that received opium-free water. After 45 days vertical and horizontal diameters of testis, number of seminiferous tubules, mean seminiferous tubule diameter, number of germ cells, height of germinal epithelium, percentage of degenerating Leydig and germ cells and glutathione density of testicular tissue (µmol/g of tissue) were compared between study groups. Results: Morphological evaluation of testicular tissue revealed a significantly higher percentage of degenerating Leydig and germ cells in the treated group compared to control group. (10.08 ± 0.351 vs. 1.83 ± 0.88, 4.50 ± 0.769 vs. 0.607 ± 0.118, respectively) (P-value<0.001 for each) Interestingly, vertical and horizontal diameter of testis, the average number of germ cells, height of germinal epithelium and number of seminiferous tubules, were significantly higher in the treated group compared to control group. Seminiferous tubule diameter and glutathione density of testicular tissue were not statistically significantly different between the groups. Conclusions: Applying a rat model, we noted that opium has a substantial effect on testicular structure and function. A significantly higher proportion of Leydig and germ cells were degenerated in treated rats despite an increase in the average number of seminiferous tubules and germ cells. These findings support the hypothesis that opium consumption adversely affects male fertility.